Bone mineral density in children with idiopathic nephrotic syndrome - Ghada Mohamed El-Mashad; Mahmoud Ahmed El-Hawy; Sally Mohamed El-Hefnawy; Sanaa Mansour Mohamed
Abstract Objectives: To assess bone mineral density (BMD) in children with idiopathic nephrotic syndrome (NS) and normal glomerular filtration rate (GFR). Methods: Cross-sectional case-control study carried out on 50 children: 25 cases of NS (16 steroid-sensitive [SSNS] and nine steroid-resistant [SRNS] under follow up in the pediatric nephrology unit of Menoufia University Hospital, which is tertiary care center, were compared to 25 healthy controls with matched age and sex. All of the participants were subjected to complete history taking, thorough clinical examination, laboratory investigations (serum creatinine, blood urea nitrogen [BUN], phosphorus [P], total and ionized calcium [Ca], parathyroid hormone [PTH], and alkaline phosphatase [ALP]). Bone mineral density was measured at the lumbar spinal region (L2-L4) in patients group using dual-energy X-ray absorptiometry (DXA). Results: Total and ionized Ca were significantly lower while, serum P, ALP, and PTH were higher in SSNS and SRNS cases than the controls. Osteopenia was documented by DXA scan in 11 patients (44%) and osteoporosis in two patients (8%). Fracture risk was mild in six (24%), moderate in two (8%), and marked in three (12%) of patients. Conclusion: Bone mineralization was negatively affected by steroid treatment in children with NS.